Are Buzzed Drivers Really the Problem: A Quasi-Experimental Multilevel Assessment of the Involvement of Drivers With Low Blood Alcohol Levels in Fatal Crashes - Stringer, Richard J. (Criminal justice policy review, 2018)
Controversy over drivers with low blood alcohol concentrations (BAC) have become a highly salient issue since the proposal to reduce the per se BAC limit to .05 for driving under the influence (DUI) convictions. However, little traffic safety, and no criminological research, has examined this phenomenon. This study fills a deficiency in the literature by utilizing quasi-experimental propensity score matching techniques in combination with multilevel modeling to examine the extent of involvement of low BAC drivers in fatal crashes. The results indicate that low BAC drivers are only involved in a very small portion of crashes and are not at fault in many. In addition, although drivers with low BAC have an increased odds of responsibility for a crash than drivers with no BAC, this increase is much lower than other factors such as age, speed, distractions, drug use, and high BAC. This study discusses the implications of focusing resources on drivers that are not considerable contributors to crashes, such as a predicted increase in arrests.